Immobilization of bone morphogenetic protein-2 to gelatin/avidin-modified hydroxyapatite composite scaffolds for bone regeneration. (April 2019) - Cheng, Cheng-Hsin; Lai, Yi-Hui; Chen, Yi-Wen; Yao, Chun-Hsu; Chen, Kuo-Yu
Bone scaffold surface characterization is important for improving cell adhesion, migration, and differentiation. In this study, bone morphogenetic protein-2 (BMP-2) was immobilized to the surface of the gelatin/hydroxyapatite composite using avidin–biotin binding system to produce a bone-tissue engineering scaffold. Firstly, hydroxyapatite particles reacted with hexamethylene diisocyanate and then the terminal group was converted into a primary amine group. Avidin was then immobilized on the surfaces of hydroxyapatite particles using N-ethyl-N′-(3-(dimethylamino)propyl) carbodiimide and N-hydroxysuccinimide as coupling agents. Gelatin was blended with avidin-modified hydroxyapatite and pure hydroxyapatite to obtain gelain/hydroxyapatite composite. The composite was then cross-linked with glutaraldehyde. Finally, biotin-conjugated BMP-2 was immobilized on the surface of the composite via avidin–biotin binding. In vitro study indicated that BMP-2-immobilized composite film had a higher ALP activity than that composite film without BMP-2. The composite scaffolds were then implanted into rabbit skulls to check bone-tissue regeneration. Ultrasound and micro-CT scans demonstrated that neovascularization and new bone formation in the BMP-2-immobilized composite scaffolds were higher than those in composite scaffolds without BMP-2. Histological evaluation result was similar to that of the micro-CT. Therefore, the surface immobilization of BMP-2 could effectively improve osteogenesis in the gelatin/hydroxyapatite composite scaffold.